2017
DOI: 10.1007/s10800-017-1114-x
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet printing infiltration of Ni-Gd:CeO2 anodes for low temperature solid oxide fuel cells

Abstract: The effect of inkjet printing infiltration of Gd 0.1 Ce 0.9 O 2-x in NiO-Gd 0.1 Ce 0.9 O 2-x anodes on the performance of symmetrical and button cells was investigated. The anodes were fabricated by inkjet printing of suspension and sol inks. Symmetrical cells were produced from composite suspension inks on Gd 0.1 Ce 0.9 O 2-x electrolyte. As-prepared scaffolds were infiltrated with Gd 0.1-Ce 0.9 O 2 ink. Increasing the number of infiltration steps led to formation of ''nano-decoration'' on pre-sintered anodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…An alternative way of controlling the wetting properties is synthesizing inks based on organic solvents. It was previously observed that EtOH based ink was shown to achieve a high degree of wetting on both metal and oxide surfaces without utilization of additional surfactants [16].…”
Section: Infiltration Strategiesmentioning
confidence: 99%
“…An alternative way of controlling the wetting properties is synthesizing inks based on organic solvents. It was previously observed that EtOH based ink was shown to achieve a high degree of wetting on both metal and oxide surfaces without utilization of additional surfactants [16].…”
Section: Infiltration Strategiesmentioning
confidence: 99%
“…However, the polarization-induced activation is generally not durable; the electrode relaxation gradually occurs after interruption of polarization. The impregnation of porous electrodes with solutions of cerium or praseodymium nitrates, which decompose to the related oxides upon heating, was found to be effective for enhancement of the electrode performance [ 7 , 8 , 9 , 10 ]. Cerium nitrate solution was successfully used for activation of Ni-cermet SOFC anodes [ 7 , 8 ], whereas the impregnation with a solution of praseodymium nitrate was reported to activate cathodes such as In 2 O 3 [ 9 ] and Pt [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The impregnation of porous electrodes with solutions of cerium or praseodymium nitrates, which decompose to the related oxides upon heating, was found to be effective for enhancement of the electrode performance [ 7 , 8 , 9 , 10 ]. Cerium nitrate solution was successfully used for activation of Ni-cermet SOFC anodes [ 7 , 8 ], whereas the impregnation with a solution of praseodymium nitrate was reported to activate cathodes such as In 2 O 3 [ 9 ] and Pt [ 10 , 11 ]. The observed decrease of the electrode polarization resistance was explained by extension of the oxygen reduction/oxidation reaction area due to infiltration of the oxide particles into the porous electrode matrix [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The second goal is to be able to monitor or predict the catalyst deposition amount by tuning just a few parameters, such as solution concentration. Although, the dripping method is the most utilized technique, there are some innovative alternative methods applied to lower the steps required to deposit material and enhance the homogeneity, such as atomic layer deposition [112,120,132,136,149], inkjet printing [134,143,144,147,177,178], etc. The dripping process requires many infiltration repetitions of low-concentration metal salt solutions to achieve sufficient solid loading to form a percolated network.…”
Section: Infiltration Methodsmentioning
confidence: 99%
“…By tuning the infiltration step or the concentration of the precursor, particles can either be deposited discretely or in a connected network. Another catalytic material doped ceria (XDC, X=Metal), attracted attention due to its flexibility of use either in the anode or cathode or even the electrolyte material [30,32,37,42,44,45,51,53,58,59,61,63,64,69,72,76,77,80,83,87,91,96,99,100,102,103,105,107,109,113,121,122,130,134,140,147] . For example, gadolinium-doped ceria (GDC) acts as an ionic conductor, and also by switching the valence character of ceria from +4 to +3 repeatedly, nanoparticles can achieve hydrogen storage capability.…”
Section: Electrochemical Performance Enhancement By Catalyst Infiltramentioning
confidence: 99%